The association between iodine intake and semen quality among fertile men in China - Yu Sun; Chen Chen; Gordon G. Liu; Meijiao Wang; Cuige Shi; Ge Yu; Fang Lv; Ning Wang; Shucheng Zhang (BMC, 2020)
Abstract Background Iodine intake is essential in the production of thyroid hormone but very few foods are rich in it. Iodine deficiency or excess iodine level may both lead to thyroid disorders, which further affects human fertility function. The objective of this study is to investigate the relationship between iodine intake and seminal parameters among fertile men in China. Methods A total of 1098 couples were recruited by trained physicians at different family planning service stations in 2015. Semen and iodine samples were obtained from male respondents. A questionnaire survey inquired about demographic information from couples. The main outcome variables of semen quality were semen volume, semen concentration, semen motility, and sperm count, and time to pregnancy. Urinary iodine concentration (UIC) was used to measure iodine levels for male respondents. Ordinary least squared regressions and logistic regressions were performed to estimate the association between iodine intake level and semen quality parameters. Results Male respondents with deficient or excess iodine levels had a 5% higher semen volume relative to those with optimal iodine intake (p < 0.1). Suboptimal iodine intake was negatively associated with semen concentration and semen counts (p < 0.01). Longer time of pregnancy was observed in iodine deficiency and excess group than those in the optimal group (p < 0.01). Conclusion In general, iodine deficiency and excess were both associated with decreasing semen quality parameters in male respondents.